INTERACTION EFFECT OF TITANIUM DIOXIDE (TiO2) AND SILICA DIOXIDE (SiO2) NANOPARTICLES ON BEAN (Phaseolus vulgaris L.) IN THE PRESENCE OF EARTHWORM (Aporrectodea calignosa) - Labiba ZERARI, Saoussene CHERNINE, Amina CHAKER, Amir BRINIS, (Chelonian Research Foundation, 2024)
The manufactured nanoparticles used in the treatment of the agricultural soils, present an impact on the human health since their residues were found to be transferred into the food chain via plants. The present work was carried out in order to evaluate the effect of some nanoparticles on a plant bean, Phaseolus vulgaris, widely consumed by humans via a chronic treatment with titanium dioxide (TiO2) (40 mg / l) and silica dioxide (SiO2) (30 mg/l) separately and in mixture with or without earthworms. At first we made a half of the seeds of bean seeds "Phaseolus vulgaris L." variety MGT NELSON under optimal conditions of humidity and temperature (25-26° C), with a watering every other day using distilled water for a period of 25 days, beyond is the treatment for a period of 20 days every other day alternating with distilled water. Tests and measurements were carried out on the soil, the plant and the earthworm: An analysis of some physico-chemical determinants of soil: pH, electrical conductivity, and cation content. Several analyzes and assays carried out on the roots and leaves of plants treated or not namely, a total protein assay, soluble sugar levels, quantification of polyphenols, catalase activity and chlorophyll content associated with this a statistical study and a histological study. A final part concerns some analyzes on this earthworm, the protein content, lipid and carbohydrate levels, CAT activity, as well as a statistical study and a histopathological study. The obtained results show a significant disturbance at the level of treated plants lightened by the presence of earthworms, since the histological study confirms it by the reduction of its sieve-vascular system. While for earthworms the presence of oxidative stress which results in the damage observed in the epidermis and the intestinal tissue studied.